Relatório de estágio curricular no Julgado de Paz de Lisboa - Feliz, Sónia Cristina Guerra (2016)
The objective of the current document is to reflect about all the experience related to the professional internship that took place in Julgado de Paz de Lisboa, under the orientation of the Teacher Mariana França Gouveia (Faculty Guider) and the judges João Chumbinho and Maria Judite Matias (Intern Guiders from Julgados de Paz). The professional internship concerns the last studying plan semester of the 2nd cycle of Law Studies in FDUNL, and his completion requires the elaboration of a report documenting all the formation process. The current internship report is about what I’ve done during the work in JP. The report is also about legal, institutional and functional context and internship characterization. It also reports about the investigation study “ Competência dos Julgados de Paz, exclusiva ou alternativa?”.